Circuito productivo sojero y conflicto agrario en la Argentina. El año 2008 como hito y punto de inflexión - Varesi, Gastón Angel (2020)
The article analyzes the soy production circuit, addressing its socio-economic and territorial dynamics, as part of a broader agribusiness subsystem. In addition, after understanding these structural anchors, we analyze the agrarian conflict of 2008, characterizing it as a milestone that established a turning point in post-convertibility Argentina. In order to accomplish this, we propose a theoretical-methodological framework that recovers concepts of the regional analysis approach and the Marxist tradition, forming a holistic and relational view that focuses on the productive processes and the dynamics of conflict, outlining an analysis of relations of forces.